ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI WILAYAH TAPAL KUDA TAHUN 2012-2018 - Annasrul Hidayatullah; Zainal Arifin; Muhammad Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi, 2021)
The  purpose of this study was to analyze the effect of Gross Domesticl Product (GDP), Human Development Index (HDI) and Minimum Wages on poverty in the Tapal Kuda area. The regression analysis used in this study is panel data with the model used is Fixed Effect. In this study using quantitative types and types of secondary data obtained from the publication of the Central Bureau of Statistics. The results showed that the variables of GDP and HDI had a negative and significant effect on poverty. While the minimum wage variable has a positive and significant effect on poverty in the Tapal Kuda area.